Analysis of the Marketing Strategy of Savings Products to Increase the Number of Customers at Bank Muamalat Indonesia KCP Stabat - Siska Muliani (Penerbit Jurnal Indonesia, 2022)
Bank is an institution in the financial sector whose function is to collect funds from the public and distribute funds to the public in the form of credit. Islamic banks are financial institutions whose processes are carried out according to Islamic principles and do not contain usury in them. Islamic banks refer to the provisions of the Koran for the rules of muamalat. Islamic banks have grown rapidly in the world since the formation of the Islamic Development Bank (IDB) in 1975. Since then it has been calculated that hundreds of Islamic banks have grown throughout the world, such as from Islamic countries and non-Islamic countries. Islamic banks have now increased their funds like conventional banks in general. Islamic banks have become collectors and distributors of Muslim funds both for purposes related to worship such as funds from infaq, sadaqah, and zakat or muamalah, namely al-wadi deposits. ah and mudharabah. One of the PT. Bank Muamalat Indonesia is PT. Bank Muamalat Indonesia KCP Stabat, has a variety of products similar to PT. Other Bank Muamalat Indonesia, both fund raising products, fund distribution products and service products. One type of fundraising product is savings. The various kinds of savings at PT. Bank Muamalat Indonesia KCP Stabat, namely general savings, including: my savings, Muamalat iB savings, Muamalat Prima iB savings, iB Muamalat Sahabat savings. The marketing strategy for Savings products carried out by Bank Muamalat KCP Stabat is based on the 4Ps (Product, Price, Place, and Promotion). As well as the promotion of savings products with the presence of the Muamalat Din application which can be used as an attraction for the public to open savings at Bank Muamalat KCP Stabat.